Correlation between Duration of the Second Stage and Pelvic Floor Muscle Strength in Primiparous Women Following Vaginal Delivery and Caesarean Section - Witono Gunawan1, TrikaIrianta2, AjardianaIdrus3, Maisuri T. Chalid4, David Lotisna2, Rina Previana3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Women underwent caesarean section tend to have higher pelvic floor muscle strength;however,pelvic floor muscle strength in women underwent caesarean section in the second stage of labor have notbeen widely studied. This study aimed to assess correlation between duration of the second stage of laborwith pelvic floor muscle strength in primiparous women underwent vaginal delivery and caesarean section.Materials and Method: In this prospective study, 58 primiparous women underwent vaginal delivery andsecond–stage caesarean section were recruited from hospitals affiliated with Hasanuddin University inMakassar, Indonesia. Pelvic floor muscle strength was measured at 6 weeks following delivery. Correlationanalysis was performed to estimate the correlation between pelvic floor muscle strength and duration of thesecond stage.Results: Demographical characteristics were similar between groups. Primiparous women in caesareansection group had longer duration of second stage than women in vaginal delivery group(206,38 + 107,66minutes versus 61,89 + 36,67, P< 0.001). Mean pelvic muscle floor strength in primiparous women underwentsecond stage caesarean section were similar to women underwent vaginal delivery(41,99 + 8,59 cm H2Oversus. 41,83 + 12,44 cm H2O, P= 0.954). Duration of the second stage had no correlation with pelvic floormuscle strength in both vaginal delivery (r= 0,248; P = 0.195) and caesarean section (r = -0,083; P = 0.669).Conclusion: Duration of the second stage may not alter pelvic floor muscle strength regardless of mode ofdelivery.